Antioxidant Activity and Brine Shrimp Lethality of Bacopa monnieri L.† - V. Krishnaraju, Alluri; Sundararaju, Dodda; V.N. Rao, Tayi; Ashok Kumar, Kommineni; V. Subbaraju, Gottumukkala (Asian Journal of Chemistry, 2010)
Various extracts of B. monnieri have shown superoxide free radical, hydroxyl radical and 1,1-diphenyl-2-picryl-hydrazyl (DPPH) radical scavenging activities and inhibition of lipid peroxidation. Alcohol extract, however, showed better antioxidant activity compared to other extracts of B. monnieri. Methanol and commercial Bacopa extracts are equipotent to amla extract in inhibition of lipid peroxidation in rat liver, but Bacopa extracts have shown superior activity in rat brain tissue. Bacopa extracts have also shown brine shrimp lethality.